Addressing the controversial origin of the marble source used in the Phoenician anthropoid sarcophagi of Gadir (Cadiz, Spain). (18th November 2020) - Lapuente, P.; Rodà, I.; Gutiérrez Garcia‐M, A.; Brilli, M.
Abstract : Dating from the fifth century bce, two Phoenician anthropoid sarcophagi, a male and a female, found in Gadir (Cadiz, Spain), are so far the most ancient marble sculptures found in the Iberian Peninsula. The identification of the source of the marble used to produce them has been a subject of controversy for several decades and has recently resurfaced when it was published that they were made by Phoenician artisans using Iberian marble from Macael. This identification is not only unreasonable from an archaeological point of view but also unsupported by any analytical data. On the contrary, as the sarcophagi belong to an Eastern Mediterranean Sidonian production, their raw material is most likely to be Greek–Minor Asian in origin. In order to shed a light on this dispute and objectively resolve the provenance of the marble, a multi‐method analytical approach was carried out. Optical microscopy, cathodoluminescence analyses, and C and O stable isotopes clarify the provenance of the marble, confirming that both singular sarcophagi were carved in a Cycladic marble, in accordance with their Sidonian style.